A rare indication for lung transplantation – pulmonary alveolar microlithiasis: institutional experience of five consecutive cases. Issue 4 (24th February 2016) - Klikovits, Thomas; Slama, Alexis; Hoetzenecker, Konrad; Waseda, Ryuichi; Lambers, Christopher; Murakoezy, Gabriella; Jaksch, Peter; Aigner, Clemens; Taghavi, Shahrokh; Klepetko, Walter; Lang, Gyoergy; Hoda, Mir Alireza
Abstract: Background: Pulmonary alveolar microlithiasis (PAM) is a rare lung disease caused by calcifications within the alveolar space. The only known effective treatment for an end‐stage PAM is lung transplantation (LuTX). Methods: We performed a retrospective chart review of all individuals that underwent lung transplantation at our center between 1989 and 2013. Five consecutive patients with PAM were identified. Results: Four females and one male with a mean age of 46.3 yr were identified. Extracorporeal membrane oxygenation (ECMO) support was required intraoperatively in four cases and post‐operatively in one case. Mean post‐operative intubation time was 3.3 (range, 2–5) d and mean intensive care unit (ICU) stay was 8.3 (range, 4–12) d. No intraoperative complications were observed. One early patient (operated in 1995) underwent acute re‐transplantation on the second post‐operative day (POD) and died from sepsis on the 11 POD. In one patient reperfusion edema was observed requiring a prolonged weaning process. No other severe perioperative complications were observed. Four of five patients are currently still alive with normal follow‐up parameters. No recurrence of PAM was observed. Conclusions: Lung transplantation is a feasible therapy option in patients with end‐stage PAM showing good post‐operative results comparable to other indications for LuTX.